Penerapan Metode Bercerita dengan Pendekatan Ramah Anak untuk Mengembangkan Bahasa Anak Usia Dini di PAUD Ar Rahman - Rizqiyatul Fadilah; Thorik Aziz (Institut Agama Islam Negeri Madura, 2024)
This study investigates the effectiveness of the storytelling method with a child-friendly approach in developing language skills in early childhood at PAUD Ar Rahman. The research employs a qualitative methodology, collecting data through participatory observation and in-depth interviews with educators and parents. The goal is to evaluate the interaction between the children and the story material and its impact on language development. The results of this study indicate that the storytelling method, when integrated into a supportive and participatory approach, significantly enhances vocabulary acquisition, listening comprehension, and children's language expression skills. Furthermore, this approach contributes to the development of social skills and empathy, affirming the positive relationship between the use of stories relevant to the children's daily experiences and their increased engagement in the learning process.